Differences between buccal and lingual bone quality and quantity of peri-implant regions. (July 2016) - Kim, Do-Gyoon; Elias, Kathy L.; Jeong, Yong-Hoon; Kwon, Hyun-Jung; Clements, Matthew; Brantley, William A.; Lee, Damian J.; Han, Jung-Suk
Abstract: The objective of the current study was to examine whether peri-implant bone tissue properties are different between the buccal and lingual regions treated by growth factors. Four dental implant groups were used: titanium (Ti) implants, alumina-blasted zirconia implants (ATZ-N), alumina-blasted zirconia implants with demineralized bone matrix (DBM) (ATZ-D), and alumina-blasted zirconia implants with rhBMP-2 (ATZ-B). These implants were placed in mandibles of six male dogs. Nanoindentation elastic modulus ( E ) and plastic hardness ( H ) were measured for the buccal and lingual bone tissues adjacent and away from the implants at 3 and 6 weeks post-implantation. A total of 2281 indentations were conducted for 48 placed implants. The peri-implant buccal region had less bone quantity resulting from lower height and narrower width of bone tissue than the lingual region. Buccal bone tissues had significant greater mean values of E and H than lingual bone tissues at each distance and healing period ( p <0.007). Nearly all implant treatment groups displayed lower mean values of the E at the lingual bone tissues than at the buccal bone tissues ( p <0.046) although the difference was not significant for the Ti implant group ( p =0.758). The DBM and rhBMP-2 treatments stimulated more peri-implant bone remodeling at the lingual region, producing more immature new bone tissues with lower E than at the buccal region. This finding suggests that the growth factor treatments to the zirconia implant system may help balance the quantity and quality differences between the peri-implant bone tissues.